2021
DOI: 10.1007/s40429-021-00398-0
|View full text |Cite
|
Sign up to set email alerts
|

The Overlap Between Problematic Smartphone Use and Problematic Social Media Use: a Systematic Review

Abstract: Purpose of Review Over the last decade, problematic smartphone use (PSU) and problematic social media use (PSMU) have emerged as new potential problematic behaviours. Several studies have suggested that smartphones are predominantly used for social purposes (i.e., using messaging apps and social networking sites). The aim of the current article is to provide a systematic review of the extant literature that has explicitly analysed the association between PSU and PSMU in order to examine study cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 67 publications
1
20
0
Order By: Relevance
“…However, the results of the study need to be interpreted in the light of some limitations. Firstly, PSMU is not classified as a disorder in any existing diagnostic system, and there is no consensus among researchers regarding the assessment of addiction-like SM use ( Marino et al, 2021 , Wegmann et al, 2022 ). Secondly, in the current study no information was collected about the amount of time spent on SM, as well as the type of activity enjoyed online, nor the mode of interaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of the study need to be interpreted in the light of some limitations. Firstly, PSMU is not classified as a disorder in any existing diagnostic system, and there is no consensus among researchers regarding the assessment of addiction-like SM use ( Marino et al, 2021 , Wegmann et al, 2022 ). Secondly, in the current study no information was collected about the amount of time spent on SM, as well as the type of activity enjoyed online, nor the mode of interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, smartphones allow for the use of a number of other non-social oriented applications and potentially problematic activities such as news consumption, and web surfing (smartphone process use). These considerations draw attention to the current debate on the overlap between the problematic use of smartphones and the problematic use of specific activities available on smartphones, such as social media apps (for a systematic review, see Marino et al, 2021).We did not find support for the hypothesis that high levels of apprehension of missing friends' rewarding experiences leads to using the smartphone as a vehicle to stay in touch with significant others-FoMO predicts PSU, but not via intense social smartphone use. One possible explanation related to the measure we used for measuring social smartphone use.…”
Section: Testing Model 2: Fear Of Not Being Up To Date→metacognitions...mentioning
confidence: 63%
“…The relationship between PIU and PSU was maintained only in girls, albeit weakly. This is surprising, especially because PSU is generally associated with the intensive use of online social networking sites (Marino et al., 2021), which is a dominant environment for peer communication where aggressive communication may occur (Martínez‐Ferrer, Moreno, & Musitu, 2018). Indeed, previous studies have found an association between social networking site use and mainly cyberbullying experiences (Craig et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies point out their convergence (Škařupová, Ólafsson, & Blinka, 2016) and that many users suffer from both issues (Lee et al., 2018). Other studies signify potential differences and the need for their differentiation (Montag, Wegmann, Sariyska, Demetrovics, & Brand, 2021): PIU is more typical for excessive gaming (Blinka et al., 2015), and PSU is almost identical to the problematic use of social networking sites (Marino, Canale, Melodia, Spada, & Vieno, 2021). While boys tend to score higher in PIU, girls tend to be higher in PSU (Choi et al., 2015).…”
Section: Introductionmentioning
confidence: 99%